Pengaruh Substitusi Tepung Talas (Colocasia Esculenta L.) Terhadap Kualitas Soft Cookies - Rintan Wilyasri; Ezi Angraini; Yuliana; Yolanda Intan Sari (Pasundan Food Technology Journal (PFTJ), 2026)
This study aimed to evaluate the effect of Belitung taro flour (Colocasia esculenta L.) substitution on the sensory quality of soft cookies. An experimental design using a Completely Randomized Design (CRD) with one factor, namely the level of taro flour substitution, was applied: 0% (X0), 50% (X1), 60% (X2), and 70% (X3). Sensory evaluation was conducted using a 7-point rating scale to assess shape, color, aroma, texture (outer crispness, inner softness, and pore structure), and taste, involving five panelists. Data were analyzed using one-way ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test when significant differences were observed. The results showed that taro flour substitution did not significantly affect the sensory attributes of shape, color, aroma, inner softness, pore structure, and taste of soft cookies. A significant effect was only observed on outer crispness, where higher levels of taro flour substitution reduced the crisp texture of the cookie surface. Descriptively, substitution levels of 50–60% provided the most balanced sensory quality. Therefore, Belitung taro flour has strong potential as a partial substitute for wheat flour up to 70% in soft cookie formulation without reducing sensory acceptability, supporting the development of local-based food diversification.